2016
DOI: 10.4187/respcare.04519
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal Administration of Antimicrobial Agents in Mechanically Ventilated Adults: An International Survey on Delivery Practices and Safety

Abstract: BACKGROUND: Intratracheal antibiotic administration is increasingly used for treating respiratory infections. Limited information is available on delivery devices, techniques, and safety. METHODS: An online survey on intratracheal administration of anti-infective agents in mechanically ventilated adults was answered by health-care workers from 192 ICUs to assess the most commonly used devices, current delivery practices, and safety issues. We investigated whether ICU usage experience (>3 y) impacted its perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 25 publications
3
22
0
1
Order By: Relevance
“…Nebulization of antibiotics in mechanically ventilated adults with respiratory infections is a practice that is increasingly used, despite a lack of standardization and limited evidence on the associated efficacy and safety [2,3]. Based on a previous systematic review and meta-analysis [7], this ESCMID panel does not support the use of nebulization of antibiotics in any of the scenarios assessed because the available evidence is weak and heterogeneous (and in some scenarios entirely absent).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nebulization of antibiotics in mechanically ventilated adults with respiratory infections is a practice that is increasingly used, despite a lack of standardization and limited evidence on the associated efficacy and safety [2,3]. Based on a previous systematic review and meta-analysis [7], this ESCMID panel does not support the use of nebulization of antibiotics in any of the scenarios assessed because the available evidence is weak and heterogeneous (and in some scenarios entirely absent).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical challenges posed by extremely-or pan-drug-resistant Gram-negative pathogens are causing significant concern for clinicians, creating situations reminiscent of the pre-antibiotic era. Therefore, despite lacking high-quality efficacy and safety data, clinicians worldwide are increasingly using antibiotic nebulization to optimize the treatment of respiratory infections in critically ill invasively mechanically ventilated adult patients [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…There are some informative reviews available covering the history and methodology associated with aerosol delivery to intubated and ventilated adult patients , and aerosol delivery in the ventilated paediatric population . Despite these reviews, a wide variety of differing drug delivery practices have been reported , indicating a disconnection between those working in aerosol research and those working in clinical areas. In this article, we review the available literature in order to provide suggestions as to how best to treat individuals requiring a variety of respiratory support.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the weak evidence in support of these indications, primarily due to the limited number of prospective randomized trials, the panel recommended against the routine use of aerosolized antibiotics for the treatment of VAT and VAP. Unfortunately, several recent surveys suggest that clinicians in many parts of the world are already employing aerosolized antibiotics in their daily practices, potentially making the current recommendations of Rello et al too little and too late [17,18].…”
mentioning
confidence: 99%